2018
DOI: 10.14740/gr1041w
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Biologics and Anti-Tumoral Immune Therapies-Associated Colitis: A Focused Review of Literature

Abstract: An increasing number of drugs including monoclonal antibodies and small molecules, either anti-inflammatory or immunity-enhancing, have been developed to treat human diseases and the number of medications in these classes is likely to expand in the future. The two most commonly used categories of such therapies are the anti-inflammatory group (anti- tumor necrosis factor (TNF) α, anti-interleukins/interleukin receptors, and anti-integrin bodies) and the anti-tumoral agents (immune checkpoint inhibitors, anti-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 73 publications
(124 reference statements)
0
26
0
Order By: Relevance
“…Similarly, a large realworld retrospective longitudinal cohort study of the incidence of IBD among patients with CIDs treated with IL-17 blockers or PDE4 inhibitors found that treatment with IL-17 antagonists was associated with more than 3fold higher odds of having IBD relative to patients naïve to biologics and patients treated with biologics not indicated for the treatment of IBD [38]. Finally, a number of studies also found that etanercept was associated with exacerbation of existing IBD or new onset IBD [21,22].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, a large realworld retrospective longitudinal cohort study of the incidence of IBD among patients with CIDs treated with IL-17 blockers or PDE4 inhibitors found that treatment with IL-17 antagonists was associated with more than 3fold higher odds of having IBD relative to patients naïve to biologics and patients treated with biologics not indicated for the treatment of IBD [38]. Finally, a number of studies also found that etanercept was associated with exacerbation of existing IBD or new onset IBD [21,22].…”
Section: Discussionmentioning
confidence: 96%
“…However, there is evidence suggesting that some of these treatments may increase the risk of developing new onset IBD or exacerbating existing IBD in patients with CIDs [12,14,15]. The use of certain biologic therapies such as etanercept (a tumor necrosis factor inhibitor) and interleukin-17 antagonists in patients with CIDs is cautioned due to possible increased risk of IBD [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Another histological pattern is "lymphocytic colitis" similar to the one observed in ipilimumab-related injury, while recurrent anti-PD1 colitis can result in IBDlike chronic active colitis [23,25]. Few cases of ICPIsinduced collagenous colitis have also been reported [26][27][28]. Concerning lymphocytic subsets, T cell population prevails in ICPIs-associated colitis.…”
Section: Discussionmentioning
confidence: 83%
“…Vedolizumab is a humanized monoclonal antibody that binds to the human α4β7 integrin, approved for use in inflammatory bowel diseases (IBD), [1]. Our patient presented with refractory erosive gingivostomatitis, a few days after the initial dose of vedolizumab.…”
Section: Introductionmentioning
confidence: 94%